Quantitative analysis of cervical vertebral maturation in Chinese adolescents based on three-dimensional morphology of cervical vertebrae - WU Yue, TANG Wen, ZHANG Yuyanran, YUAN Weiyu, PAN Yifei, CHEN Xinyu, XU Haiyang, LYU Yunfan, IZADIKHAH Iman, CAO Dan, XIE Lizhe, YAN Bin (Editorial Office of Stomatology, 2024)
Objective To investigate associations between three-dimensional(3D) morphology of cervical vertebrae and skeletal maturation by cone-beam computed tomography(CBCT) and establish corresponding regression models for quantitatively evaluating cervical vertebral maturation(CVM). Methods The analyzed sample consisted of 358 CBCT images (175 male, 183 female), of which 277 images were randomly selected as the model development group and 81 as the performance test group. Twenty-one 3D morphological parameters were defined and measured, incorporating all parts of the cervical vertebrae, including the cervical vertebral bodies, transverse processes, spinous processes, pedicles, lamina, and articular processes. The cervical vertebral maturation index (CVMI) was determined by experienced orthodontists as reference standard. Spearman's rank correlation coefficient and multivariable stepwise regression analysis were used to identify the associations and build regression models. The performance test group was employed to examine each model's reliability. Paired-samples Wilcoxon signed-rank test compared the CVMI of the model prediction with the reference standard. Results Three-dimensional morphological changes in various parts of the cervical vertebrae correlated with CVMI (P<0.05). Six 3D morphometric parameters were each recognized for male and female models, three of which were identical. The adjusted R2 was 0.899 for males and 0.902 for females, with corresponding accuracies of 85.0% and 85.4%, respectively. These models showed no difference as compared with the reference standard (P>0.05). Conclusion New associations were found between 3D morphology of cervical vertebrae and skeletal maturation. The 3D-driven morphometric CVM assessment method and corresponding regression models exhibited good credibility and high consistency with experts.